2018
DOI: 10.1080/02601370.2018.1489425
|View full text |Cite
|
Sign up to set email alerts
|

Abyssal lines and cartographies of exclusion in migration and education: towards a reimagining

Abstract: Educational institutions across the Western world, from schools through to universities are increasingly being drawn into highly ideological spaces of immigration control, integration and securitisation. This paper outlines the complex contours of this 'education-migration nexus' and contributes to the critique of the way that education is becoming yoked to different political and social agendas. It also seeks to offer an analysis of the way in which the experiences, knowledges and practices of those from non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…However, Gibb (2015) explains that programs are largely designed and delivered based on universal or national understandings of language and literacy. Therefore, they diminish immigrants' and refugees' embodied ways of knowing and being (Morrice, 2019). Cambodian refugees, upon resettlement in Canada, were incorporated in a language regime driven by government-constructed competency standards .…”
Section: Discussion and Implications For Social Workmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Gibb (2015) explains that programs are largely designed and delivered based on universal or national understandings of language and literacy. Therefore, they diminish immigrants' and refugees' embodied ways of knowing and being (Morrice, 2019). Cambodian refugees, upon resettlement in Canada, were incorporated in a language regime driven by government-constructed competency standards .…”
Section: Discussion and Implications For Social Workmentioning
confidence: 99%
“…According to Gibb (2015) standards based on reading, writing, listening and speaking proficiency, invariably position language as mechanistic and ignore cultural, political and social norms associated with it. Thus, in a globalized world, language, literacy and issues of newcomer integration in host societies highlight both difference and systems of inequality (Blommaert, 2010;Gibb, 2010;Morrice, 2019). Significantly, first-generation Cambodian Canadians' experiences have revealed that literacy and language are intertwined with social power relations which relegate them to the margins of Canadian society (Thobani, 2007).…”
Section: Discussion and Implications For Social Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Gibb, 2015, Morrice, 2014, Webb, 2015, Wildemeersch, 2017. This is not surprising, as Morrice (2019) asserts that current western-centric framing reflects colonial logics and privileges, employing an assimilationist approach: 'Integration has become an identity issue with migrants having to prove their willingness to integrate by attending classes and passing tests' (Morrice, 2014, p. 156). Migrants are held responsible to demonstrate their willingness and ability to adapt (Morrice, 2019).…”
Section: Adult Education In Times Of Migration: Between Instrumental Learning and Transformative Learningmentioning
confidence: 99%